cpPredictor: a web server for template-based prediction of RNA secondary structure - Jelínek, Jan; Pánek, Josef (Bioinformatics (Oxford, England), 2019)
SUMMARY: We present the cpPredictor webserver that implements a novel template-based method for prediction of secondary structure of RNA. The method outperforms available prediction methods as it uses RNA structures of related molecules, either predicted or experimentally identified, as structural templates. The server aims at three major tasks: i) prediction of RNA secondary structures that are difficult to predict by available methods, ii) characterization of uncharacterized RNAs as compatible or incompatible with a chosen template structure and iii) an identification of the most relevant structure among different candidate structures of a single RNA ambiguously predicted by available methods. The web server is accompanied with a comprehensive documentation. AVAILABILITY AND IMPLEMENTATION: The web server is freely available at http://cppredictor.elixir-czech.cz/. The source code of the cpPredictor algorithm is freely available from the webserver under the Apache License, Version 2.0.
Keywords: konformace nukleové kyseliny; Software; sekundární struktura proteinů; Protein Structure, Secondary; RNA; software; Algorithms; internet; sekvenční analýza RNA; Sequence Analysis, RNA; Nucleic Acid Conformation; Internet; algoritmy